Sosialisasi Sistem Jaminan Halal (SJH) untuk Produk Lumpiah Basah Produksi UMKM Markaz Kabayan, Darussalam, Banda Aceh - Satriana, Satriana; Nilda, Cut; Murlida, Eva; Widayat, Heru Prono (JURNAL PENGABDIAN MAHAKARYA MASYARAKAT INDONESIA, 2023)
Micro, small, and medium enterprises (MSMEs) are one of the national economys fastest-growing and consistent business sectors. The development and growth of MSME and cooperative actors are very significant and continue to increayearry yearly, including in Banda Aceh City. MSMEs that produce food and beverages are listed as one of the businesses with potential that will continue to increase because food and beverages are basic of human needs. However, not all food and drinks are clearly halal because not all are accompanied by halal labels and certificates. The partner who assisted in the socialization of this service is Markaz Kabayan MSME. This MSME located in Banda Aceh City produces Bandungs typical wet spring rolls. Markaz Kabayan currently does not have a halal certificate and does not aware of the application for halal certification. The service team wants to help so that the products from Markaz Kabayan can be more guaranteed and attract consumers who want to buy their products. This service activity went well and smoothly. The owner of Markaz Kabayan strongly desires to apply for halal certification following the procedures explained by the service team.